Inverse cationic ITP for separation of methadone enantiomers with sulfated β‐cyclodextrin as chiral selector. Issue 5 (22nd October 2018) - Mikkonen, Saara; Caslavska, Jitka; Gebauer, Petr; Thormann, Wolfgang
Abstract: Chiral ITP of the weak base methadone using inverse cationic configurations with H + as leading component and multiple isomer sulfated β‐CD (S‐β‐CD) as leading electrolyte (LE) additive, has been studied utilizing dynamic computer simulation, a calculation model based on steady‐state values of the ITP zones, and capillary ITP. By varying the amount of acidic S‐β‐CD in the LE composed of 3‐morpholino‐2‐hydroxypropanesulfonic acid and the chiral selector, and employing glycylglycine as terminating electrolyte (TE), inverse cationic ITP provides systems in which either both enantiomers, only the enantiomer with weaker complexation, or none of the two enantiomers form cationic ITP zones. For the configuration studied, the data reveal that only S‐methadone migrates isotachophoretically when the S‐β‐CD concentration in the LE is between about 0.484 and 1.113 mM. Under these conditions, R‐methadone migrates zone electrophoretically in the TE. An S‐β‐CD concentration between about 0.070 and 0.484 mM results in both S‐ and R‐methadone forming ITP zones. With >1.113 mM and < about 0.050 mM of S‐β‐CD in the LE both enantiomers are migrating within the TE and LE, respectively. Chiral inverse cationic ITP with acidic S‐β‐CD in the LE is demonstrated to permit selective ITP trapping and concentration of the less interacting enantiomer of a weak base.